SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN GURU TELADAN DI MADRASAH TSANAWIYAH PONDOK PESANTREN AN-NUR TANGKIT MUARO JAMBI MENGGUNAKAN METODE SMART - Purnama, Fery; Supriadi, Dede (JURNAL AKADEMIKA, 2020)
An-nur Islamic boarding school is an integrated Islamic educational institution that uses the school system (Manhaj Khalafi) and other boarding systems (Manhaj Salafi) in Tsanawiyah Madrasah Pondok (MTs) An-nur Islamic School in Tuar Muaro Jambi is different from the Madrasah Tsanawiyah Pondok Pesantren give awards to teachers who have worked so well in terms of teaching that can be an example for other teachers in teaching. So far, the assessment of model teacher elections conducted by the school only pays attention to and observes all teachers while in the school environment so that it is still subjective ie there are no clear parameters in the assessment. Then it is necessary to build a tool in the form of a decision support system that can help the school in determining the selection of suitable teacher candidates to receive an award as a model teacher, and can take into account all the criteria that support decision making. the method used in making the decision to give a model teacher is SMART (Simple Multi Attribute Rating Technique). The application used to assist data processing is Microsoft Visual Basic .Net. With the making of a decision support system using the SMART method, it is hoped that it can optimize the selection of teachers who are entitled to receive the model teacher award, so that the selection can run effectively and efficiently.